Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV MARIA S. MERIAN during cruise MSM04/4b - Gerhard Fischer (PANGAEA, 2025)
Raw bathymetry data were collected using the ship extquotesingles own Kongsberg EM120 multibeam echosounder during the RV MARIA S. MERIAN cruise MSM04/4b. The cruise took place between 2007-03-19 and 2007-04-01 (Las Palmas, Spain – Las Palmas, Spain). The main goal of the MSM04/4 cruise was to continue long-term investigations of recent environmental conditions and particle dynamics, as well as to recover sediment cores for paleoclimatic reconstructions at the NW African continental margin. During Leg MSM04/4b, bathymetry data were collected in the area north of the Canary Islands and off Cape Blanc. One sound velocity profile (SVP) was taken on 2007-02-28 during Leg MSM04/4a, which is integrated into the raw .all files. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).